Parental involvement in Children’s learning: Experience from parents on supervising children’s learning at home - Basnyat, Samjhana (ILAM इलम, 2025)
It is believed that parental involvement positively affects children's learning at home. Parents take an active role in supporting the learning of their children at home. As a result, the purpose of this study is to examine how parents are involved in their children's at-home learning and what roles they play in supporting their learning. The primary focus of this study is on parental involvement in assessing children's learning at home (motivators, facilitators, sources of knowledge, and coordinators) in children's learning at home as proposed by Epstein (2011). The study's participants consist of nine parents from Bhaktapur—six mothers and three fathers—who have enrolled their kids in a community school that offers the Basic level. This study was carried out using interviews and applied a qualitative approach. The results demonstrate that parents keep focus on the academic progress of their children at home. Typically, parents help their children study at home, provide them with learning guidance, and get them ready for school. Additionally, they play the duties of parents in their children' at-home learning by performing as coordinators, motivators, facilitators, and knowledge providers. Since this study focuses on family involvement in basic school-level children’s learning, it is recommended that future studies concentrate on parental involvement in education at other levels.